In Vitro and In Vivo Antitumor Effect of Anti-CD33 Chimeric Receptor-Expressing EBV-CTL against CD33+ Acute Myeloid Leukemia. (5th January 2012) - Dutour, A.; Marin, V.; Pizzitola, I.; Valsesia-Wittmann, S.; Lee, D.; Yvon, E.; Finney, H.; Lawson, A.; Brenner, M.; Biondi, A.; Biagi, E.; Rousseau, R.
Abstract : Genetic engineering of T cells with chimeric T-cell receptors (CARs) is an attractive strategy to treat malignancies. It extends the range of antigens for adoptive T-cell immunotherapy, and major mechanisms of tumor escape are bypassed. With this strategy we redirected immune responses towards the CD33 antigen to target acute myeloid leukemia. To improve in vivo T-cell persistence, we modified human Epstein Barr Virus-(EBV-) specific cytotoxic T cells with an anti-CD33.CAR. Genetically modified T cells displayed EBV and HLA-unrestricted CD33 bispecificity in vitro . In addition, though showing a myeloablative activity, they did not irreversibly impair the clonogenic potential of normal CD34 + hematopoietic progenitors. Moreover, after intravenous administration into CD33 + human acute myeloid leukemia-bearing NOD-SCID mice, anti-CD33-EBV-specific T cells reached the tumor sites exerting antitumor activity in vivo . In conclusion, targeting CD33 by CAR-modified EBV-specific T cells may provide additional therapeutic benefit to AML patients as compared to conventional chemotherapy or transplantation regimens alone.